PERFORMANCE OF FOOD AND BEVERAGE COMPANIES BEFORE AND DURING THE CORONA VIRUS PANDEMIC - Hastuti, Rini Tri; Andrew, Richard; Cahyani, Felita (Graduate Program of Universitas Tarumanagara, 2024)
The spread of Corona virus is happening so fast in almost all countries in the world, including Indonesia. The effect of this pandemic is felt by several industrial sectors, including companies that run their businesses in the food and beverage sector. The purpose of this study is to test and analyze the differences in the performance or financial performance of food and beverage companies listed on the Indonesia Stock Exchange before and during the Corona virus outbreak when viewed from net profit margin (NPM), debt to asset ratio (DAR), total asset turnover (TATO), and current ratio (CR). The purposive sampling method is applied in the sample selection process. The samples processed in this study were from 8 companies. This study uses secondary data in the form of financial statement data for food and beverage companies from 2018 to 2021. The data is divided into two periods, namely 2018 to 2019 for the period before the Corona virus pandemic, and 2020 to 2021 as the period during the Corona virus pandemic. Hypothesis testing uses a paired sample t-test, and the data is processed with the help of IBM SPSS Version 26 software. The results revealed that there were differences in NPM and TATO before and during the Corona virus pandemic, and there were no differences in DAR and CR before and during the Corona virus pandemic.